2018
DOI: 10.1080/24749508.2018.1508980
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of trees in a community managed forest: the case of Komolchori VCF, Khagrachari, Bangladesh

Abstract: Natural forest in the Chittagong Hill Tracts (CHTs) of Bangladesh is degrading due to various reasons. Village common forest (VCF) in CHTs is one of the successful forest management schemes without government intervention. This research was conducted in the Komolchori VCF, Khagrachari, Bangladesh to delineate its tree diversity status. A total of 921 individuals belonging to 55 species were found from 25 randomly studied plots. The highest basal area and relative dominance were recorded for Terminalia belliric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
14
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 20 publications
(32 reference statements)
4
14
1
Order By: Relevance
“…Cluster analysis of the current study showed G. nervosa is the most dominant species in the study area whereas, different ecological studies also find similar trend of results among the floral groups (Chowdhury, Islam et al, 2018;Erenso, Vegetati Marya, & Wendawek, 2014;Flinn & Lechowicz, 2008;Sajib & Uddin, 2016). In addition, the regeneration of the forest is affected not only by environmental factors but also by anthropogenic activities (De Cauwer, 2016;Kuma & Shibru, 2015).…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…Cluster analysis of the current study showed G. nervosa is the most dominant species in the study area whereas, different ecological studies also find similar trend of results among the floral groups (Chowdhury, Islam et al, 2018;Erenso, Vegetati Marya, & Wendawek, 2014;Flinn & Lechowicz, 2008;Sajib & Uddin, 2016). In addition, the regeneration of the forest is affected not only by environmental factors but also by anthropogenic activities (De Cauwer, 2016;Kuma & Shibru, 2015).…”
Section: Discussionsupporting
confidence: 68%
“…Diversity indices indicate vital information about the composition and current status of vegetation in a study area (Chowdhury, Islam et al, 2018). The diversity indices, e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The study revealed average family size was higher (5.78) in Hridoy Member Para in comparison to Haduk Para (5.25) whereas average earning was more (2.3) in Hridoy Member Para compared to Haduk Para (2.1) ( Table 2). Besides, average annual income among the respondents was higher in Haduk Para (1,25,400 Tk.) than Hridoy Member Para (1, 02, 340 Tk.)…”
Section: Background Characteristics Of Respondentsmentioning
confidence: 93%
“…Community-based practices including indigenous knowledge, behavior, and perception of conservation of resources are highly related to livelihood of local people and several studies confirm this for coastal areas [17,18,19,20] and for hilly tracts in Bangladesh [9,21]. However, while several studies have been conducted on community-based adaptation from the perspective of CHTs and in other parts of Bangladesh [5,6,8,10,13,22] and on species diversity of VCFs and other forests in Bangladesh [23,24,25] few studies on community dependency on VCF are available. Therefore, this study was conducted to evaluate the dependency of the community and participation in and attitudes about conservation practices of Haduk Para and Hridoy Member Para VCF of Khagrachari.…”
Section: Introductionmentioning
confidence: 99%